2018
DOI: 10.1016/j.conctc.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying and visualizing site performance in clinical trials

Abstract: BackgroundOne of the keys to running a successful clinical trial is the selection of high quality clinical sites, i.e., sites that are able to enroll patients quickly, engage them on an ongoing basis to prevent drop-out, and execute the trial in strict accordance to the clinical protocol. Intuitively, the historical track record of a site is one of the strongest predictors of its future performance; however, issues such as data availability and wide differences in protocol complexity can complicate interpretat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 3 publications
0
12
0
3
Order By: Relevance
“…Both our own work in discovery, 25 clinical, 26,27 and outcomes research 28 and work in other scientific domains 29 have found that human intuition married to meaningful and actionable visualizations can lead to more optimal outcomes than a purely statistical or computational approach. Our primary goal in designing our RBM solution was to allow clinical staff who may not have formal training in data mining, informatics, or statistics to readily identify patterns in the data, confirm or challenge their assumptions, and make more informed decisions.…”
Section: T a G G E D H 1 Introductiont A G G E D E N Dmentioning
confidence: 93%
“…Both our own work in discovery, 25 clinical, 26,27 and outcomes research 28 and work in other scientific domains 29 have found that human intuition married to meaningful and actionable visualizations can lead to more optimal outcomes than a purely statistical or computational approach. Our primary goal in designing our RBM solution was to allow clinical staff who may not have formal training in data mining, informatics, or statistics to readily identify patterns in the data, confirm or challenge their assumptions, and make more informed decisions.…”
Section: T a G G E D H 1 Introductiont A G G E D E N Dmentioning
confidence: 93%
“…Furthermore, demanding protocols could also negatively influence clinical trial site performance, increasing the level of stress for trial site personnel [ 35 ]. High complexity and demanding trial site tasks may impact the performance of clinical trial sites, where low- and non-performing sites are already a challenge for the clinical trial industry [ 11 ]. In an analysis from 2018 conducted by the Boston Consulting Group and KMR Group, data from more than 75000 sites were used to examine site performance and underlying drivers of success.…”
Section: Discussionmentioning
confidence: 99%
“…Armed with such knowledge, a growing number of pharmaceutical companies and contract research organizations (CRO’s) are working to optimize recruitment for clinical trials through optimizing study designs in order to improve feasibility and ease site and subject participation burden [ 40 ]. The declining productivity of drug development has intensified the interest in digital tools and other technologies that may improve trial efficiency [ 11 ]. In a systematic review and meta analysis from 2019, we found that targeting participants using online remedies was an effective tool for patient recruitment in clinical trials, as online recruitment was superior to traditional in-clinic recrutiment in regards to both time-efficiency and cost-effectiveness [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigator portal presented here is part of a broader clinical trial management suite, known as Xcellerate, that uses advanced data integration, analytics, and visualization capabilities to improve patient safety, data quality, and protocol compliance throughout the clinical development process and enable greater transparency and oversight of study conduct and performance. 4 9 Inspired from previous work in discovery, 10 clinical, 11 , 12 and outcomes research, 13 this solution consists of a number of end-user applications connected to a clinical data repository that supports near-real-time acquisition, mapping, and integration of clinical trial data from any germane source, including laboratory test results, the subject matter of the present work. The Xcellerate Investigator Portal leverages the same architectural and web design principles to provide secure online access to laboratory results, manuals, and training materials through an intuitive interface that enhances user adoption, productivity, and collaboration.…”
Section: Introductionmentioning
confidence: 99%